Alternative de valorificare artistică a Tap dance - Strâmtu, Adrian (Symbolon, 2018)
Artistic Use Alternatives of Tap Dance Understanding the tap dance complexity requires a multidisciplinary analysis, which exploits elements of disciplines like actor’s art, stage improvisation and choreography to characterize tap dance specific art, and its means of artistic expression. The artistic complexity and expressiveness of tap dance are provided by several elements, the most important being: a) the size of the actor’s involvement through: the creative artistic approach; personal style; personal footprint; body expression; choreography and improvisation; b) the contributions of musical sequences: jazz improvisation, jam session, Shim Sham; c) the contributions of the intrinsic properties of tap dance - to which we will refer in this study. In a global approach, tap dancing can be portrayed as an independent artistic phenomenon and as an artistic phenomenon complementary to the theatre.